Development of Kanomtuay Product for Health - Charoenphun, Narin; Kiawvijit, Jirawan; Deeharing, Suwanee (Journal of Food Technology, Siam University, 2018)
This research aimed to optimize the ingredients to produce lower and upper layers of a healthy Thai dessert called “kanomtuay”. The nine formulations of the lower layer of the dessert consisting of water, sugar and fresh longan flesh were studied by using Mixture Design. Sensory evaluation was conducted by 30 untrained panelists. It was found that a suitable formulation of the lower layer was 17.5% water, 22.5% sugar and 60% fresh longan flesh. This formulation had the highest score of taste, texture and overall liking (7.80±0.66). Furthermore, the suitable ratio of coconut milk substituted by soy milk in the upper layer of kanomtuay was studied. Coconut milk was replaced by soy milk at 0, 25, 50, 75 and 100%. The result indicated that 50% substitution with soy milk showed a good appearance of kanomtuay. The upper layer had canary yellow color, moderately oily fracture and soft texture. Moreover, there was no separation between lower and upper layer of kanomtuay. It had overall liking score of 7.23±0.63 (like moderately). Interestingly, low temperature (4°C) can extend the shelf life of kanomtuay for seven days. Meanwhile, the sample was spoiled at room temperature (30°C) during storage in two days. In conclusion, the healthy kanomtuay product is a new interesting alternative for consumers.